Optical properties and photoluminescence of copper nitride thin film prepared by reactive DC sputtering - Mohammed Ariff, Noor Azizun (2013)
This research was conducted to prepare copper nitride thin films on glass substrates by reactive DC sputtering technique using a copper plate and nitrogen gas at 20 Pa as source. The Argon pressure 1x 10-1 mbar and DC voltage of 0.5 kV at room temperature. The deposition time varies from 1.0 hour to 3.5 hours at interval of 0.5 hour. The thickness of films was measured using Ellisopmeter, UV-VIS 3101 Spectrophotometer to measure the optical properties of refractive index,n, transmittance, absorbance and reflectance in the visible light region and the photoluminescence property using Luminescence Spectrometer LS55.The films obtained were yellow to reddish-brown depending on the deposition time. For longer deposition time, the thin films turned thicker reddish-brown colour. Thickness of films obtained were in the range 1219.4 nm to 1227.0 nm and the refractive index, n, was about 3.80, constant for all samples. The transmittance increased but absorbance and reflectance decreased as the thickness increased over the wavelength range.. The avaege optical band gap energy, Eg obtained in range of 1.65 to 1.94 eV. The averange emmission peak for maximum intensity was about 419.0 nm obtained in the photoluminescence emission for all samples. This shows that the luminescence light is that of violet light.